The internet as a subject in schools - Mitra, Sugata (Prospects (Paris), 2022)
Education that does not include an understanding of the Internet and how to live with it, is deficient. This article describes how the Internet can be learned in schools, what the curriculum for such learning should be at various stages of schooling, what pedagogical methods should be used to achieve the learning objectives and what methods should be used to assess the learning outcomes. It is based on decades of experiments and observations by the author and others.